2011
DOI: 10.1002/jssc.201100547
|View full text |Cite
|
Sign up to set email alerts
|

Preparative isolation and purification of senkyunolide‐I, senkyunolide‐H and ferulic acid from Rhizoma Chuanxiong using counter‐current chromatography

Abstract: Three active compounds, senkyunolide-I, senkyunolide-H and ferulic acid (FA), were successfully isolated and purified from the extracts of Rhizoma Chuanxiong by counter-current chromatography (CCC). Based on the principle of the partition coefficient values (k) for target compounds and the separation factor (α) between target compounds, the two-phase solvent system that contains n-hexane-ethyl acetate-methanol-water at an optimized volume ratio of 3:7:4:6 v/v was selected for the CCC separation, and the lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The structure of isolated compound with melting point of 168° C is presented in Figure 1. The isolated compound was elucidated by, 1 HNMR, 13 CNMR, IR and MS as well as comparison of the data with those reported in the literature (12). The analytical data were as follows:…”
Section: Resultsmentioning
confidence: 88%
“…The structure of isolated compound with melting point of 168° C is presented in Figure 1. The isolated compound was elucidated by, 1 HNMR, 13 CNMR, IR and MS as well as comparison of the data with those reported in the literature (12). The analytical data were as follows:…”
Section: Resultsmentioning
confidence: 88%
“…Besides, our previous research showed that, by comparing to raw Chuanxiong Rhizoma (RCR), the contents of butylidenephthalide, ligustilide senkyunolide A and ferulic acid were increased in wine-processed Chuanxiong Rhizoma (WCR). Additionally, these four components have many biological properties and pharmacological functions [15][16][17][18]. Therefore, they were selected as the target analytes in our experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, this compound can be metabolized to butylidenephthalide, senkyunolide I (M156), and senkyunolide H (M155) in vivo [15]. The three natural ingredients produce various pharmacological activities in cerebral blood vessels, the general circulatory system and immune system including spasmolysis contraction effects [16,17], inhibitory effects of platelet aggregation [18] and anti-proliferative activity, and thus improve the therapeutic effect on patients. Cnidilide (M93, OB = 77.55%) and spathulenol (M169, OB = 82.37%) also closely correlate with the smooth muscle relaxant action, and thereby have the strongest spasmolytic activity [19].…”
Section: Resultsmentioning
confidence: 99%